2014
DOI: 10.1007/s10555-014-9514-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological functions of MTA family of proteins

Abstract: Although the functional significance of the MTA family of chromatin remodeling proteins in the pathobiology of cancer is fairly well recognized, the physiological role of MTA proteins continues to be an understudied research area and is just beginning to be recognized. Similar to cancer cells, MTA1 also modulates the expression of target genes in normal cells either by acting as a corepressor or coactivator. In addition, physiological functions of MTA proteins are likely to be influenced by its differential ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 58 publications
0
29
0
3
Order By: Relevance
“…presence of histone deacetylases (HDACs) (Bowen et al, 2004), but the presence of HDACs per se does not ensure transcriptional repression because studies on the NuRD interaction with the GATA-1/FOG-1 transcription factor complex support transcriptional activation (Miccio et al, 2010). At this time it is unclear if AhR recruitment of MTA2 occurs in the context of a complete NuRD complex capable of coactivation as described for GATA-1/FOG-1, or if MTA2 is functioning in an NuRD-independent capacity akin to that proposed for MTA1 (Sen et al, 2014). Kim et al (2014) recently demonstrated that two NuRD subunits, CHD4 and MTA2, associated constitutively with the DNA-bound CLOCK-BMAL1 to drive target gene expression, and that transcriptional repression only occurred once the negative regulator, PERIOD, recruited the remaining NuRD complex components to CLOCK-BMAL1 DNA binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…presence of histone deacetylases (HDACs) (Bowen et al, 2004), but the presence of HDACs per se does not ensure transcriptional repression because studies on the NuRD interaction with the GATA-1/FOG-1 transcription factor complex support transcriptional activation (Miccio et al, 2010). At this time it is unclear if AhR recruitment of MTA2 occurs in the context of a complete NuRD complex capable of coactivation as described for GATA-1/FOG-1, or if MTA2 is functioning in an NuRD-independent capacity akin to that proposed for MTA1 (Sen et al, 2014). Kim et al (2014) recently demonstrated that two NuRD subunits, CHD4 and MTA2, associated constitutively with the DNA-bound CLOCK-BMAL1 to drive target gene expression, and that transcriptional repression only occurred once the negative regulator, PERIOD, recruited the remaining NuRD complex components to CLOCK-BMAL1 DNA binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the MTA family members have emerged as one of the most important regulatory molecules with both redundant and non-redundant activities in both physiological and cancer cells (Sen et al, 2014a, Sen et al, 2014b). A large body of work over the years suggests that the MTA family members regulate numerous cellular pathways with roles in cancer progression and metastasis (Li and Kumar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of work over the years suggests that the MTA family members regulate numerous cellular pathways with roles in cancer progression and metastasis (Li and Kumar, 2015). However, because MTA family members are ubiquitously expressed and natural levels of MTA family members are equally important for several essential physiological functions (Sen et al, 2014a), the authors believe the MTA family members may also follow a nomenclature that is based on their structural elements, rather than the current nomenclature derived from the historical cloning of the founding member MTA1 - as a differential expressed gene from rat metastatic mammary gland tumors (Toh et al, 1994). However, this is more of a philosophical point of continuing scientific debate as the functions of MTA family members are independent of what we name these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the target molecule MTA1 is a well studied nuclear receptor coregulator in malignant disorders and has been shown to be induced in response to growth factors (32). Several recent studies have reported the tissue-specific functions of MTA1 and have been shown to act both as a coactivator and a corepressor depending on the tissue type (42). In view of this, we tested the idea whether MTA1 could be up-regulated in the dopaminergic neurons by growth factors, thereby increasing the levels of TH.…”
Section: Discussionmentioning
confidence: 99%